Poor Diet Leading to the Increasing Risk of Atherosclerosis in the World - Bhusal, Bijaya (Journal of Cardiology and Cardiovascular Medicine, 2024)
Atherosclerosis Ischemic Cardiovascular Disease (ASICD), one of the leading causes of global deaths, is mainly caused due to the development of plaque on the inner walls of arteries of the human heart. Ischemia refers to the lack of enough oxygen (O2), nutrient delivery, and improper waste removal in the cardiac cells. About 90% of cardiovascular diseases in the present world are due to the formation of lipid/cholesterol-based plaques that can form under the lining of the smooth epithelial blood cells. In the US, a study published in the Journal of the American College of Cardiology estimated that poor diet is responsible for about 45% of Cardiovascular Disease. Atherosclerosis doesn’t cause much effect until and unless the plaque becomes unstable due to the accumulation of thrombus that shows Acute Coronary Syndrome. Acute Coronary Syndrome is the result of blockage of blood vessels leading to Myocardial Infarction (Unstable Angina Pectoris). Cardiac Cells require a sufficient amount of Oxygen to function properly. Thus, the demand and supply of oxygen to the cardiac cells should be properly balanced. Atherosclerosis Ischemic Cardiovascular syndrome can worsen if the person is more involved in exercise or emotional stress because at that time their body requires higher oxygen but blood flow gets disrupted due to the formation of plague. Later in the paper, we will discuss the New York Heart Association classification, followed by the top 3 poor diets that are considered to be increasing the cases of cardiovascular disease around the world.